Solvent switchable dual emission from a bichromophoric ruthenium–BODIPY complex. Issue 87 (15th September 2015) - Martin, Aaron; Byrne, Aisling; Dolan, Ciarán; Forster, Robert J.; Keyes, Tia E.
Abstract : A ruthenium(ii ) polypyridyl–BODIPY dyad is presented which exhibits a solvent switchable dual emission. Abstract : A ruthenium(ii ) polypyridyl–BODIPY dyad is presented which exhibits a solvent switchable dual emission. Intense oxygen sensitive emission from the ruthenium centre and O2 independent emission from the BODIPY centre, are both observed in organic media. In aqueous media, the BODIPY emission is reversibly switched off leaving only a ruthenium centred emission. The materials are interesting both as self-referenced O2 probes and for cell/tissue imaging.